Endovascular Renal Artery Stent Retriever Embolectomy in a Young Patient With Cardiac Myxoma: Case Report and Review of the Literature. (January 2018) - Silva, Michael A.; See, Alfred P.; Shah, Samir K.; Khandelwal, Priyank; Patel, Nirav J.; Lyu, Heather; Menard, Matthew T.; Aziz-Sultan, Mohammad Ali
Purpose: Cardiac myxomas are common tumors of the heart with disproportionate impact on young patients, occasionally with dramatic systemic dissemination of tumor emboli with catastrophic multiorgan system ischemia. The coincident comorbidities can increase the risk of traditional treatments for tumor embolus in each region. Case report: A young patient with previously unknown cardiac myxoma presented with seizure and was found to have stress cardiomyopathy, multiple cerebral large vessel occlusions with acute ischemic stroke, bilateral lower extremity tumor emboli and rhabdomyolysis, and renal tumor embolus with acute tubular necrosis. We describe a multidisciplinary approach applying cerebrovascular stent retriever devices in tumor embolectomy of the renal artery of a young patient with systemic morbidity, preventing safe laparotomy for open surgical tumor embolectomy. Conclusion: We describe 2-month renal function outcomes and the considerations in applying a neuroendovascular mechanical thrombectomy device within the renal artery. This was a radiographically successful technique and her renal function appears to be improving at the 2-month follow-up, although this is complicated by other renal insults and support.